Effects of sleep disruption on stress, nigrostriatal markers, and behavior in a chronic/progressive MPTP male mouse model of parkinsonism. Issue 12 (18th September 2019) - Xu, Mo; Bohlen, Jerry K.; Moore, Cynthia; Nipper, Michelle A.; Finn, Deborah A.; Jones, Carolyn E.; Lim, Miranda M.; Meshul, Charles K.
Abstract: Sleep complaints are an early clinical symptom of neurodegenerative disorders. Patients with Parkinson's disease (PD) experience sleep disruption (SD). The objective of this study was to determine if preexisting, chronic SD leads to a greater loss of tyrosine hydroxylase (TH) within the striatum and the substantia nigra following chronic/progressive exposure with the neurotoxin, 1‐methyl‐2‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP). Male mice underwent chronic SD for 4 weeks, then injected with vehicle (VEH) or increasing doses of MPTP for 4 weeks. There was a significant decrease in the plasma corticosterone levels in the MPTP group, an increase in the SD group, and a return to the VEH levels in the SD+MPTP group. Protein expression levels for TH in the striatum (terminals) and substantia nigra pars compacta (dopamine [DA] cell counts) revealed up to a 78% and 38% decrease, respectively, in the MPTP and SD+MPTP groups compared to their relevant VEH and SD groups. DA transporter protein expression increased in the striatum in the MPTP versus VEH group and in the SN/midbrain between the SD+MPTP and the VEH group. There was a main effect of MPTP on various gait measures (e.g., braking) relative to the SD or VEH groups. In the SD+MPTP group, there were no differences compared to the VEH group. Thus, SD, prior to administration of MPTP, has effects on serum corticosterone and gait but more importantly does not potentiate greater loss of TH within the nigrostriatal pathway compared to the MPTP group, suggesting that in PD patients with SD, there is no exacerbation of the DA cell loss. Abstract : TH+/dopamine cell counts of the SNpc showed a 36% decrease ( p = 0.0036) and a 38% decrease ( p = 0.0021) in both the MPTP and SD+MPTP groups compared to the VEH and SD groups, respectively. Photos of TH− labeled SNpc from each treatment group are shown above the graph at 5× and 20× magnification (black arrows point to TH‐ir SNpc neurons and red arrows point to Cresyl Violet SNpc neurons).